The Effect Of Laughing Therapy Towards Stress Level Of Elderly In Upt Panti Sosial Rehabilitasi Lanjut Usia Mulia Dharma Provinsi Kalimantan Barat - Jamilah, Jamilah (ProNers, 2020)
Background: Indonesia is an old structured country because more than 7% of the citizens are elderly people. One of the main purposes that must be achieved by the Ministry of Health is to increase the life quality of elderly people. The Disorders which are usually faced by the elderly people are the stress. The stress that happens constantly can harm the lives elderly people, which is why elderly peoples' level of stress must be stable. One way to lower elderly peoples' level of stress is by a laughing therapy. Purpose: To understand the effects of laughing therapy towards stress level of elderly   in UPT Panti Sosial Rehabilitasi Lanjut Usia Mulia Dharma Provinsi Kalimantan Barat. Method: Quantitative method which uses quasy experimental study design with pre and post test control group study design on 32 respondents. The instrument being used is the Stress Assessment Questionnaire (SAQ) and the data analysis being used is Wilcoxon test. Result: The results of this study are Ha accepted with the result that there is an effect of giving laugh therapy to stress in elderly. And there are differences between intervention group and control group. Conclusion: There is an effect in the laugh therapy on the stress level of elderly in UPT Panti Sosial Rehabilitasi Lanjut Usia Mulia Dharma Provinsi Kalimantan Barat, which means the laugh therapy can be recommended to help lowering the stress level of elderly.